Analysis Efficiency of Islamic Bank in Indonesia and Saudi Arabia With Data Envelopment Analysis Approach - Ilham Hibatullah; Anggita Nurcahyani (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2022)
This study aims to measure the level of performance efficiency of Islamic banks in Indonesia and Saudi Arabia from 2018 to 2020; and Analyzing improvement targets that can be carried out by Islamic banks in Indonesia and Saudi Arabia to achieve optimum performance using the Data Envelopment Analysis (DEA) method. Data analysis was carried out using the MaxDEA program version 8.2. The sampling technique in this study was done by purposive sampling. The object of this research is the 4 largest Islamic banks in each country. Input and Output Variable data are obtained from financial reports from 2018 - 2020. The results show that the average efficiency value of Indonesian Islamic Banks is higher than the average efficiency of Saudi Arabian Islamic Banks in the 2018 and 2019 periods. using both the CRS and VRS models. As for the 2020 period, the opposite applies where the average efficiency value of Saudi Arabian Islamic Banks outperforms Indonesian Islamic Banks with the same two measurement models. As a whole, the average efficiency value of Saudi Arabian Islamic Banks is superior to the CRS model, while the Indonesian Islamic Bank's VRS model has a higher average efficiency value.